Anomalous grain boundary conduction in BiScO3-BaTiO3 high temperature dielectrics. (1st September 2021) - Li, Linhao; Roncal-Herrero, Teresa; Harrington, John; Milne, Steven J.; Brown, Andy P.; Dean, Julian S; Sinclair, Derek C
Abstract: A combination of X-ray diffraction, analytical-electron microscopy, differential scanning calorimetry, impedance spectroscopy and electromotive force measurements (for oxide-ion transport number measurements, tion ) are used to report on the influence of a small amount of a continuous Bi2 O3 -rich phase along the grain boundaries in sample composition x = 0.4 (BS0.4 BT) of the high temperature dielectric solid solution series, x(BiScO3 )-(1-x)(BaTiO3 ). Its presence produces a dramatic change in conductivity of two orders of magnitude and a switch in tion over the range 600 - 800 °C that is not observed for other ceramics with lower BiScO3 content. Below 700 °C the grain boundaries in BS0.4 BT act as electrically blocking layers and dominate the impedance of the ceramics. In contrast, at > 800 °C the grain boundaries become highly conductive due to a polymorphic phase transition to, and melting of δ-Bi2 O3 which results in the current percolating along the grain boundaries and therefore avoiding the grains. The value of tion increases from 0.13 at 600 °C to near unity at 800 °C for BS0.4 BT, consistent with oxide ion conduction due to the presence of liquid Bi2 O3 at grain boundary regions. This behaviour was reproduced by adding a small excess of 3 wt% Bi2 O3 into x = 0.3 (BS0.3 BT) samples to induce a Bi2 O3 -rich grain boundary phase, not otherwise present in this composition. Graphical abstract: Image, graphical abstract